2017
DOI: 10.1158/1538-7755.disp16-a61
|View full text |Cite
|
Sign up to set email alerts
|

Abstract A61: African American college women knowledge and attitudes toward human papillomavirus (HPV) and cervical cancer screening

Abstract: BACKGROUND: A major public health concern is the growing incidence of the sexually transmitted human papillomavirus (HPV) infection. The highest rate of HPV is found in college-age students with persistent infection noted in young African-American women (AAW). Certain oncogenic strains of HPV can lead to cervical cancer, and in the United States, AAW are more likely to die of cervical cancer than any other racial/ethnic group. While the causes of this disparity is multifactorial, past studies indicate that you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results of our study can be compared to other studies that were conducted among university students in America, South Africa and Ghana. One of the cervical cancer studies was conducted with African American women at a HBCU in the mid-Atlantic region of the United States that were between the age of 18 and 21 (Bowen-Reid et al 2017). The results of their study indicated that the individual item analysis suggested that there were deficits in basic knowledge about cervical cancer (etiology of HPV, transmission of HPV, screening strategies and prevention strategies) among the participants.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study can be compared to other studies that were conducted among university students in America, South Africa and Ghana. One of the cervical cancer studies was conducted with African American women at a HBCU in the mid-Atlantic region of the United States that were between the age of 18 and 21 (Bowen-Reid et al 2017). The results of their study indicated that the individual item analysis suggested that there were deficits in basic knowledge about cervical cancer (etiology of HPV, transmission of HPV, screening strategies and prevention strategies) among the participants.…”
Section: Discussionmentioning
confidence: 99%